Empowerment of Farming Group in Manufacture of Organic Fertilizer and Pesticide based on Animal Stomach Organs Waste from Grass Plant - Wijaya, Adi; Sutaryo, Sutaryo; Yuswanto, Adi; Setiawan, Wahyu; Hidayah, Chusnul (Bulletin of Community Engagement, 2023)
The community service carried out in Rukti Basuki Village, Rumbia District, Central Lampung Regency. These activities took place at the house of the chairman of the Rukti Basuki village farmer group through outreach to the farming community both those who are members of farmer groups and individual farming communities regarding the manufacture of liquid organic fertilizer by utilizing organic materials, which is very easy to find around us like healthy grass. The objectives of this activity are 1) To provide understanding and skills for farming communities so they can make liquid organic fertilizer from grass-based ingredients; 2) Providing understanding so that farmers maximize the use of organic fertilizers rather than chemical fertilizers; 3) Providing skills to farmers to utilize the grass around us or on the land we plant into organic fertilizer which so far has been underused by farmers; and 4) Help increase farmers' income from the agricultural sector. The method used ABCD (Asset Base Community Development), based on the strengths and assets owned by the community. The results obtained from this counseling activity included: the farmers who participated in the counseling were able to produce liquid organic fertilizer from agricultural waste, the participants were able to pack it properly and were able to apply it. Keywords: Liquid Organic Fertilizer, Empowerment of Farming Group, Grass Water